PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMA MUHAMMADIYAH BANGKINANG - Fatiha Jumalfi; Zulfah; Astuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the effect of the Jigsaw cooperative learning model on students’ mathematical communication skills at SMA Muhammadiyah Bangkinang. The study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Pretest and Posttest Control Group Design. The population consisted of all eleventh-grade students at SMA Muhammadiyah Bangkinang in the 2024/2025 academic year. The sample was selected using purposive sampling, consisting of two classes: class XI IPA 1 as the experimental group taught using the Jigsaw cooperative learning model (30 students) and class XI IPA 2 as the control group taught using conventional learning methods (29 students). The research instrument was a mathematical communication skill test consisting of five essay questions on the topic of Matrices, administered before and after the treatment. The results showed a significant difference between the mathematical communication skills of students taught using the Jigsaw model and those taught with conventional learning. This was proven by the Independent Sample t-test, which obtained a significance value of 0.000 < 0.05, indicating that the Jigsaw cooperative learning model had a significant effect on students’ mathematical communication skills. The effect size (Cohen’s d) was 2.46, which falls into the very large category. Furthermore, the N-Gain analysis showed an average score of 0.7517 for the experimental class (high/effective category) and 0.4650 for the control class (moderate category). These findings indicate that the Jigsaw cooperative learning model is highly effective and strongly influences the improvement of students’ mathematical communication skills, particularly in explaining mathematical ideas, situations, and relations both orally and in writing.